2003
DOI: 10.1080/1357628031000066651
|View full text |Cite
|
Sign up to set email alerts
|

Changing Practice in Residential Aged Care Using Participatory Methods

Abstract: The main findings of the project indicate that using a process that encourages staff involvement in identification of issues and actions can facilitate change in the practice of resident care. The action research groups identified specific gaps in knowledge and skill leading to targeted education that addressed areas of need. The importance of presenting information and learning opportunities for staff in a variety of formats was also recognized, as was the importance of organizational context, management supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Six organizational enablers were identified: the availability of organizational resources (n = 24), organizational culture supporting frontline workers’ creativity, entrepreneurial thinking and willingness to improve their workplace (n = 24) and management support (n = 22). For instance, providing frontline actors with resources could require the allocation of human resources (eg, 88 , 93 ), funding (eg, 63 , 89 ) or time for innovation (eg, 72 ), or investing in training of frontline actors (eg, 81 , 87 ). Also, systems that facilitate and stimulate EDI were a noteworthy organizational enabler, found in 18 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six organizational enablers were identified: the availability of organizational resources (n = 24), organizational culture supporting frontline workers’ creativity, entrepreneurial thinking and willingness to improve their workplace (n = 24) and management support (n = 22). For instance, providing frontline actors with resources could require the allocation of human resources (eg, 88 , 93 ), funding (eg, 63 , 89 ) or time for innovation (eg, 72 ), or investing in training of frontline actors (eg, 81 , 87 ). Also, systems that facilitate and stimulate EDI were a noteworthy organizational enabler, found in 18 studies.…”
Section: Resultsmentioning
confidence: 99%
“…It could also mean involving staff from other health disciplines and managers in solving problems (eg, 15 ) by sharing better ways of conducting frontline activities. 81 A second team-level benefit was a team approach to problem solving (n = 2), which stimulated discussion, innovation and changed the way employees saw and solved problems by creating a sense of common purpose (eg, 39 , 85 ).…”
Section: Resultsmentioning
confidence: 99%
“…When planning such activities, workload pressures and time available for staff to attend training need to be considered [14]. Training informed by action research can result in changing practice [44], and its usefulness in promoting acceptance of health technologies should be explored [45], especially because of its philosophical similarities with principles of coproduction [20].…”
Section: Xsl • Fomentioning
confidence: 99%
“…The research team (researchers and sector partners) worked together to utilize an integrated knowledge translation (KT) approach where users of research were involved in the research process through collaboration with researchers [9]. This approach has some similarities with participatory action research methods which has been used in previous research studies in LTC [10-12] and supports a culture of using feedback to improve performance [13]. In a recent systematic review, Jamtvedt et al found that audit and feedback was an effective KT intervention in improving professional practice [14].…”
Section: Introductionmentioning
confidence: 99%